A Masterpiece of Omani 17th Century Architecture: The palace of Imam Bilarab Bin Sultan Al-Yaaraba at Jabrin - Galdieri, Eugenio (The Journal of Oman Studies, 1975)
Much of the information found in the following article will also be found in the technical report sent by the author to the authorities of the Sultanate of Oman after his visit in May 1974, and in the preliminary report which is to appear in East and West, the journal of the Instituto Italiano per il Media ed Estremo Oriente.